Hubungan umur ibu, usia kehamilan dan konsumsi tablet Fe dengan kejadian anemia pada ibu hamil di Puskesmas Kartadewa Kabupaen PALI tahun 2023 - Rafika, Arroza; Riski, Meriska (NHM PRESS, 2023)
Anemia in pregnant women is a national problem that contributes to maternal and fetal mortality and morbidity, 40% of pregnant women worldwide experience anemia. Factors that influence the occurrence of anemia in pregnancy include age, gestational age, mother's education, family income, spacing of pregnancies, parity, consumption of iron supplement tablets (TTD), and medical history. The purpose of this study was to determine the relationship between maternal age, gestational age and consumption of Fe tablets with the incidence of anemia in pregnant women at the Kartadewa Health Center in PALI Regency in 2023. The study design used an analytic survey with a cross sectional approach. The population in this study were pregnant women who came to check their pregnancies at the Kartadewa Health Center in PALI Regency when the study was conducted in January-April 2023, totaling 424 people. The sampling technique in this study was carried out by means of systematic random sampling with a total sample of 81 respondents. Data collection uses a checklist sheet. Data analysis used univariate analysis and bivariate analysis using the chi square test. The results of the study showed that there was a relationship between maternal age (p value = 0.004), gestational age (p value = 0.006) and consumption of Fe tablets (p value = 0.014) with the incidence of anemia in pregnant women at the Kartadewa Health Center, PALI Regency, in 2023. It is hoped that the results of this study can be an illustration for the puskesmas to be able to increase pregnant women's knowledge about anemia such as by providing counseling about iron supplementation consumed during pregnancy and health workers are expected to empower the community to utilize existing land such as planting vegetables and conveying that food is nutritious.